Sleep and cancer: Synthesis of experimental data and meta-analyses of cancer incidence among some 1, 500, 000 study individuals in 13 countries. (20th April 2016) - Erren, T.C.; Morfeld, P.; Foster, R.G.; Reiter, R.J.; Groß, J.V.; Westermann, I.K.
ABSTRACT: Sleep and its impact on physiology and pathophysiology are researched at an accelerating pace and from many different angles. Experiments provide evidence for chronobiologically plausible links between chronodisruption and sleep and circadian rhythm disruption (SCRD), on the one hand, and the development of cancer, on the other. Epidemiological evidence from cancer incidence among some 1 500 000 study individuals in 13 countries regarding associations with sleep duration, napping or "poor sleep" is variable and inconclusive. Combined adjusted relative risks (meta-RRs) for female breast cancer, based on heterogeneous data, were 1.01 (95% CI: 0.97–1.06). Meta-RRs for cancers of the colorectum and of the lung in women and men and for prostate cancer were 1.08 (95% CI: 1.03–1.13), 1.11 (95% CI: 1.00–1.22) and 1.05 (95% CI: 0.83–1.33), respectively. The significantly increased meta-RRs for colorectal cancer, based on homogeneous data, warrant targeted study. However, the paramount epidemiological problem inhibiting valid conclusions about the associations between sleep and cancer is the probable misclassification of the exposures to facets of sleep over time . Regarding the inevitable conclusion that more research is needed to answer How are sleep and cancer linked in humans? we offer eight sets of recommendations for future studies which must take note of the complexity of multidirectional relationships.